Erosion Analysis With Geographic Information System On Watershed Area of Tapin Dam, South Kalimantan - Yanuar A. Pratama; Ira Widyastuti; Deliana Mangisu; Davy I. R. Jansen (Institut Teknologi Sepuluh Nopember (ITS), 2025)
Population growth in the Tapin Dam watershed area causes increasing land needs and changes in land function. Changes in land use and high rainfall can cause erosion, which causes sedimentation in rivers and shallowing of the Tapin Reservoir so that the service life of the reservoir is reduced. The importance of good land conversion management and the existence of national strategic infrastructure in the form of dams that need to be maintained for sustainability. A study was conducted to determine the value of the critical level of land and the amount of erosion in the Tapin Dam watershed. Based on the USLE formula using GIS analysis, four USLE method parameters are required, namely rainfall erosivity, soil erodibility map, land use map, and slope map. The overlay process is carried out to obtain the value of the amount of erosion to calculate the sediment transport ratio that occurs. The results of this study are the value of the erosion rate in the Tapin Dam watershed of 15,424.28 tons/ha/year and the amount of sedimentation released is 8,892,228.83 tons/year or 637.35 tons/ha/year.